2022
DOI: 10.3389/fpsyg.2022.884242
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Best Predictors of Paralinguistic Comprehension and Production of Emotions in Communication in Adults With Moderate Intellectual Disability

Abstract: Paralinguistic comprehension and production of emotions in communication include the skills of recognizing and interpreting emotional states with the help of facial expressions, prosody and intonation. In the relevant scientific literature, the skills of paralinguistic comprehension and production of emotions in communication are related primarily to receptive language abilities, although some authors found also their correlations with intellectual abilities and acoustic features of the voice. Therefore, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…Gender also had no discriminant significance. This is in accordance with other studies that found no effect of gender on specific aspects of pragmatics in TD participants ( 46 , 58 ), participants with schizophrenia ( 59 ), and participants with ID ( 44 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Gender also had no discriminant significance. This is in accordance with other studies that found no effect of gender on specific aspects of pragmatics in TD participants ( 46 , 58 ), participants with schizophrenia ( 59 ), and participants with ID ( 44 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, our results indicate that the level of paralinguistic abilities distinguishes between the mentioned groups, which is in line with the results of other studies in which participants with schizophrenia ( 19 , 38 , 40 ), and participants with ID ( 41 43 ), had worse results than TD participants in this domain of pragmatics. Searching for predictors of worse achievements in identifying and producing emotions in adults with ID, Calić et al ( 44 ) found that receptive language skills were a significant predictor of paralinguistic comprehension of emotions. Other authors also point out the significance of receptive vocabulary, especially the one related to naming emotions in emotion recognition tasks in children with Down syndrome ( 45 ).…”
Section: Discussionmentioning
confidence: 99%